The Importance of Guanxi: A Case Study of An Overseas Chinese Firm in Bangkok - Chaikitpattana, Panmuk (2009)
The notion of guanxi has caught attentions from a large number of scholars. It is viewed as a social network that bases on the norm of favours exchange which does not confine only in social aspect – it also extends to politic and business context. This paper is based on business context though it also touches socio-cultural aspect as it is inevitable for guanxi. However, instead of looking at a broad picture, the paper specifically stresses on the role of guanxi in an overseas Chinese business in Bangkok.